Perception of Organizational Politics, Psychological Safety, and Work Efforts of Senior High School Teachers - Lebbaeus Asamani; Bakari Yusuf Dramanu; Emilyn Ofosu-Amaah (European Scientific Journal, ESJ, 2020)
Politics is a phenomenon that can be experienced wherever there are more than two people present, and schools or work organizations are no exceptions. This paper focuses on investigating the extent to which Ghanaian Senior High School teachers’ perceptions of organizational politics and psychological safety relate to each other, and how it influences the teachers’ work efforts. A cross-sectional research design was used, which involves 275 teachers conveniently sampled from public senior high schools in the Tamale Municipality of Ghana. Standardized self-report questionnaires were adapted to collect the data, and it was analyzed using standard multiple linear regression. The results indicated that perception of organizational politics is a significant predictor of self-report work efforts of Senior High School teachers, but psychological safety was not. The results further showed that all the three dimensions of politics perception measured in the study significantly predict work efforts. This is with general political behaviour being the most significant predictor. Curiously, psychological safety perception had a significant positive relationship with politics perception. The findings from the current study suggest that perception of workplace politics is a critical determinant of attitude and behaviour of individuals at work, including work efforts. Among others, the paper recommends that pragmatic measures must be put in place to minimize workplace politics and perception ofsame in order to enhance work efforts in the workplace.